Public attitude towards food waste: The case of Lithuania - Skaidrė Žičkienė; Ala Kovierienė; Vaiva Griščiūtė (Economic and Environmental Studies (E&ES), 2020)
The purpose of the research is to investigate consumers' perception concerning food wastage and their awareness of economic, social and environmental costs concerning the issue. The research focused on the concept of food waste in context of consumers' attitude regarding this problem. Comparative analysis, synthesis and evaluation of scientific literature and legal documents, statistical data collection and analysis was performed together with the results of on-line survey of 500 households representing 1494 inhabitants from all Lithuanian counties. Data was analysed using statistical package for the social sciences (SPSS): descriptive statistics, frequencies, crosstabs. Lithuanians discard relatively small amounts of wholesome edible food in comparison with averages for EU 27, but most of them have the limited knowledge of the meaning of "best-before" dates, consumers are strongly influenced by retail promotions, and wasting food for them is primarily associated with a waste of money. State waste management policy is focused on waste sorting, while this research provides the evidence that households are insufficiently informed about economic, social and environmental costs concerning food waste. This underlines the necessity to review the current state policy with emphasis on public education as an important factor in minimizing household food waste. Lithuanians recognize that the consumers are mostly responsible for food waste, but food wasting is treated mainly as financial lost. The added value of this article is the proposal to create information campaigns that will cause a sense of guilt for food squandering.
Keywords: Q53; Q56; Q58; 330; waste management; food waste; consumer behaviour; households